Attempt of Escape in The Country Girls Trilogy by Edna O´Brien - Egrtová, Aneta (Univerzita Pardubice, 2012)
The main subject of this bachelor paper is the analysis of The Country Girls Trilogy, including The Country Girls, The Lonely Girls and Girls in Their Married Bliss, by Edna O'Brien. The initial part of this work is focused on Ireland in the 1950s and 1960s. Women's status in the society and the Irish attitude to contemporary writers are discussed in detail. In the following part, the actual analysis of the novels is conducted. The analysis deals with the attempt to escape and with the controversial themes which outraged the society in Ireland.
Pokus o útěk v trilogii Venkovské Dívky od Edny O'Brien
Keywords: O'Brien, Edna; Trilogie Vesnické Dívky; kontroverze; útěk; postavení žen; Country Girls Trilogy; controversy; escape; women's status